Pengaruh Media Kolase Berbasis Budaya Terhadap Perkembangan Motorik Halus Anak Kelas B1 RA Miftahul Ulum Pandanarum Kabupaten Mojokerto: The Effect of Culture Based Collage Media on Children’s Fine Motor Development in Class B1 RA Miftahul Ulum Pandanarum Mojokerto Regency - Rilla Ristyaningrum; Dwi Bhakti Indri M (Jurnal Intelek Insan Cendikia, 2024)
Abstract Children's fine motor development must be maximized properly. There are various kinds of learning media that can develop fine motor skills in children, one of which is using culture-based collage media. Culture-based collage media, in addition to learning about collages, also learn and introduce to children one of the cultural relics in Trowulan, namely Bajang Ratu Temple. Learning using culture-based collage media is expected to be one of the alternatives in the learning process in the classroom. The formulation of the problem in this study is how the influence of culture-based collage media in improving the fine motor development of children in class B1 RA Miftahul Ulum Pandanarum?, what is the procedure of using culture-based collage media on improving the fine motor development of children in class B1 RA Miftahul Ulum?. This study uses quantitative research with the type of experimental research using a one group pretest-posttest design research design with the aim of determining the influence of the use of culture-based collage media on fine motor development. The results of the study showed that the influence of the use of culture-based collage media on fine motor development had a Sig value of the T test of 0.000 < 0.05, and a Sig value of the normality test of 0.200 > 0.05. So it can be concluded that there is an influence of the experimental method using collage media on children's fine motor development. Keywords: Fine Motor Development, Collage Media, Culture-Based